1999
DOI: 10.1046/j.1440-1681.1999.03062.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Extracellular Atp and Shear Stress Regulate the Release of Nitric Oxide in Rat Caudal Artery

Abstract: 1. To elucidate the physiological role of nitric oxide (NO) in regulating vascular tone, the effects of NG-nitro-L-arginine methyl ester (L-NAME), an NO synthase inhibitor, on the vasoconstrictor response to noradrenaline (NA) in rat caudal artery was examined. 2. NG-Nitro-L-arginine methyl ester significantly potentiated the NA-induced increase in perfusion pressure in the perfused caudal artery, but did not affect the NA-induced contraction in caudal artery ring preparations. In addition, an increase in perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Our goal was to clarify a signaling pathway that remains unknown in many types of cells, including those of the thick ascending limb. In vascular endothelial cells, ATP released by physical and chemical stimuli increases endothelium-derived NO (22). Similarly, ATP released from red blood cells in the lung vasculature stimulates NO production by endothelial cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Our goal was to clarify a signaling pathway that remains unknown in many types of cells, including those of the thick ascending limb. In vascular endothelial cells, ATP released by physical and chemical stimuli increases endothelium-derived NO (22). Similarly, ATP released from red blood cells in the lung vasculature stimulates NO production by endothelial cells (37).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular purinergic signaling by ATP and adenosine has been hypothesized to play a central role in modulation of skeletal muscle and renal blood flow and glomerular filtration rate in the kidney (19). Recent evidence also has suggested that "cross talk" may exist between purinergic signaling and nitric oxide signaling in vascular beds (22,24,29). These issues require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…ATP release is potentiated by the Ca 2ϩ agonists ionomycin and thapsigargin. Because agonists that increase cytosolic Ca 2ϩ have profound effects on endothe-lial cell function, signaling, and production and on release of vasoactive mediators such as nitric oxide (22,24), we examined the effect of Ca 2ϩ agonists on ATP release across the apical membrane of HUVEC monolayers. Ionomycin (2 M), a Ca 2ϩ ionophore that promotes Ca 2ϩ influx into the cell from extracellular stores, elicited an immediate increase in ATP release (Fig.…”
Section: Endothelial Cells In Primary Culture Form Resistive Monolayementioning
confidence: 99%
“…ATP and shear stress (known to release ATP from endothelial cells, see Burnstock, 1999) release NO from rat tail artery endothelial cells, resulting in vasodilatation (Kwon et al, 1999). Hypotonic stress increased the [Ca 2+ ] i and outflow of ATP from endothelial cells of the rat tail artery, as well as increasing cell volume (Shinozuka et al, 2001).…”
Section: B Rat Tail Arterymentioning
confidence: 99%